THE NANTU PLATYCERIUM GRANDE (POLYPODIACEAE), A NEW GENERIC RECORD OF PLATYCERIUM IN SULAWESI, INDONESIA - Dedy Darnaedi; Lynn Clayton (BRIN Publishing (Penerbit BRIN), 2020)
DARNAEDI, D. & CLAYTON, L. 2020. The Nantu Platycerium grande (Polypodiaceae), a new generic record of Platycerium in Sulawesi, Indonesia. Reinwardtia 19(2): 81‒85. ‒‒ Platycerium grande (Fée) Kunze was discovered for the first time in Indonesia at the Nantu Forest, Gorontalo Province, Sulawesi. In this paper we document this discovery by providing a description and illustration of this species, as well as some brief ecological notes. Furthermore this is a new generic record of Platycerium in Sulawesi, Indonesia.